2014
DOI: 10.1007/s00044-014-1261-0
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay directed isolation of a novel anti-inflammatory cerebroside from the leaves of Aerva sanguinolenta

Abstract: This paper attempts to evaluate the antiinflammatory potential and the possible mechanism of action of the leaf extracts and isolated compound(s) of Aerva sanguinolenta (Amaranthaceae), traditionally used in ailments related to inflammation. The anti-inflammatory activity of ethanol extract (ASE) was evaluated by acute, subacute and chronic models of inflammation, while a new cerebroside ('trans', ASE-1), isolated from the bioactive ASE and characterized spectroscopically, was tested by carrageenan-induced mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…javanica have demonstrated its anti-inflammatory and antioxidant activity (Al-Fatimi et al 2007;Elaseed et al 2015). Preclinical studies have demonstrated that some species of this genus such as Aerva lanata, Aerva sanguinolenta have analgesic and anti-inflammatory effects (Sharma et al 2011;Mandal et al 2015). Phytochemical investigations on these plants revealed the presence of various flavonoids, terpenoids, alkaloids, tannins, saponins, carbohydrate, and phenolic compounds (Emam 1999;Kumar et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…javanica have demonstrated its anti-inflammatory and antioxidant activity (Al-Fatimi et al 2007;Elaseed et al 2015). Preclinical studies have demonstrated that some species of this genus such as Aerva lanata, Aerva sanguinolenta have analgesic and anti-inflammatory effects (Sharma et al 2011;Mandal et al 2015). Phytochemical investigations on these plants revealed the presence of various flavonoids, terpenoids, alkaloids, tannins, saponins, carbohydrate, and phenolic compounds (Emam 1999;Kumar et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A result in Yoshiyuki Mizushina s study 27 , one glucosyl compound, cerebroside from soybean showed a positive association with the in vivo inhibition of TPA 12-O tetradecanoylphorbol-13-acetate -induced inflammation in mouse ear. A new cerebroside isolated from ethanol extract of leaves of Aerva sanguinolenta showed significant inhibition of the expressions of iNOS and COX-2, and the down-regulation of the expressions of IL-1β, IL-6, IL-12 and TNF-α in LPS-stimulated macrophages via the inhibition of COX-2-mediated PGE 2 release 28 . Cerebroside D 29 reduced the levels of TNF-α, IFN-γ and IL-1β in intestinal tissue of mice with experimental colitis in a concentrationdependent manner, accompanied with markedly increased serum level of IL-10, providing a novel approach to treatment of colonic inflammation.…”
Section: Disscussionsmentioning
confidence: 93%
“…[6][7][8] Only 1% of plant source has been evaluated till date for research, thus lot more to be investigated. Amaranthus viridis (Baun note), [9][10][11][12] Aerva sanguinolenta (Lal bishalyakarani) [13][14][15] and Cynodon dactylon (Durba grass) [16][17][18] are widely and easily grown, all season, hardy plant with wild cultivation status. Table 2.…”
Section: Introductionmentioning
confidence: 99%